2023
DOI: 10.1111/os.13637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adding Morphine to Periarticular Infiltration Analgesia Combined with Single Dose Epidural Morphine in Total Knee Arthroplasty: A Randomized Controlled Study

Abstract: Objective: Morphine plays an important role in postoperative analgesia after total knee arthroplasty (TKA). However, there are limited data that investigate the administration ways of morphine. To evaluate the efficacy and safety of adding morphine to periarticular infiltration analgesia (PIA) combined with single-dose epidural morphine for the patients undergoing TKA. Methods:In total, 120 patients with knee osteoarthritis who underwent the primary TKA from April 2021 and March 2022 were randomized into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…Previous systematic reviews on periarticular morphine have identified a scarcity in the number of studies examining peri/intra-articular morphine [ 70 ]. An equivalent number of studies examined in Table 6 showed benefit [ 32 , 47 , 71 73 ] and no difference [ 74 78 ] in pain scores. The duration of pain improvement varied between 2 and 24 h [ 32 , 47 , 71 73 ].…”
Section: Morphinementioning
confidence: 99%
See 3 more Smart Citations
“…Previous systematic reviews on periarticular morphine have identified a scarcity in the number of studies examining peri/intra-articular morphine [ 70 ]. An equivalent number of studies examined in Table 6 showed benefit [ 32 , 47 , 71 73 ] and no difference [ 74 78 ] in pain scores. The duration of pain improvement varied between 2 and 24 h [ 32 , 47 , 71 73 ].…”
Section: Morphinementioning
confidence: 99%
“…An equivalent number of studies examined in Table 6 showed benefit [ 32 , 47 , 71 73 ] and no difference [ 74 78 ] in pain scores. The duration of pain improvement varied between 2 and 24 h [ 32 , 47 , 71 73 ]. Most studies showed a better range of motion with Morphine usage [ 47 , 74 78 ].…”
Section: Morphinementioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, betamethasone dipropionate is only slightly water soluble, thus serving temporarily as a local reserve and providing a continuous anti-inflammatory effect to locally damaged tissue 16 , 21 . Ropivacaine, a new longer acting local anesthetic, is the drug of choice for regional analgesia and postoperative pain management as it is not lipophilic and is more selective for motor nerves 23 . Ropivacaine exclusively blocks sensory-motor nerve separation at a very low concentration by blocking nerve excitation conduction with the reversible inhibition of sodium ion channels in the neuronal membrane 24 , making early rehabilitation possible.…”
Section: Introductionmentioning
confidence: 99%